Communal farmers buy and sell over the Net - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Communal farmers buy and sell over the Net , Namibian Economist, July 2002 Farmers in Namibia are expected to benefit from a computer-based information network that will enable them to receive information on crop and livestock prices.